Unitized Configuration Design of Thermally Stable Composite Polymer Electrolyte for Lithium Batteries Capable of Working Over a Wide Range of Temperatures. Issue 7 (18th April 2019) - Li, Ruguang; Wu, Dabei; Yu, Le; Mei, Yueni; Wang, Libin; Li, Heng; Hu, Xianluo
Abstract : Solid‐state electrolytes that can meet the requirements of high‐safety lithium batteries at high temperature aroused much attention in electrochemical energy storage.Nevertheless, the low ionic conductivity at ambient temperature and poor mechanical strength limit their practical applications. Through unitized configurationdesign, herein, a unique safe and flexible composite polymer electrolyte membrane comprising of inorganic ceramic particles (Li6.75 La3 Zr1.75 Nb0.25 O12, LLZNO), polyvinylidene fluoride (PVDF), and lithium perchlorate (LiClO4 ) are fabricated. Benefitting from the strongly coupled effects via interfacial chemical reactions and the synergistic effects between LLZNOand PVDF, the LLZNO‐based composite electrolyte wetted by ionic liquid exhibits a high ionic conductivity of 1.5 × 10 −3 S cm −1 at 25 °C. Moreover, the electrolyte is able to be thermally stable at relatively high temperatures. A LiFePO4 (+) // Li (−) lithium battery using the as‐prepared LLZNO‐based composite electrolyte achieves a good electrochemical stability at ambient temperature, 80 °C and even 120 °C. This work provides an effective way to the fabrication of high‐performance, flexible electrolyte membranes for lithium batteries and other energy‐storage devices that are capable of working over a wide range of temperatures Abstract : A strategy of unitized configuration design is developed for fabricating a thermally stable composite polymer electrolyte (CPE) membrane made of Li6.75 La3 Zr2 Nb0.25 O12 particles and PVDF. The as‐fabricated CEP possesses high ionic conductivity and enhanced refractory capability, which is a promising candidate for advanced high‐performance and safe batteries capable of working over a wide range of temperatures.